Morphological, Syntactic Structure of Euphemisms Characteristic to Two-Based Noun Groups and Their Semantic Analysis (Texas Journal of Philology, Culture and History, 2023)
In this article, the morphological and syntactic structure of the euphemisms of the two-base noun group and their semantic analysis are made.